Infidel Deathbeds: Irreligious Dying and Sincere Disbelief in Nineteenth-Century America - Kime, Bradley (Church history, 2017)
This article inquires into the piecemeal, provisional de-marginalization of American irreligion and analyzes the social stakes and strategies of dis/belief's invocation during the long nineteenth century. It does so by considering the era's corpus of American deathbed narratives. It argues that late-century irreligionists mimed and subverted the deathbed strategies of their Christian detractors to convince a skeptical American audience to concede the contested sincerity of their disbelief. For much of the nineteenth century, Christian-produced infidel deathbed narratives mapped the mixture and multiplicity of inner irreligion and interrogated the sincerity of disbelief. In response, irreligionists—initially ambivalent about the interpretability of the deathbed—eventually came to invest it with as much power to prove sincerity as had American Christians. In the last quarter of the nineteenth century, irreligionists developed a nationwide network of irreligious dying and selectively, strategically deployed the deathbed's accrued power to prove the uniform sincerity of their disbelief. By the turn of the century, they had largely neutralized the derisive force of the infidel deathbed genre, leaving disbelief a partially, provisionally less marginal and less multiplex marker in American society, and re-tethering themselves to their Christian detractors in the process.